Evaluasi efektivitas pengelolaan sampah di TPS 3R: Studi kasus Kota Magelang - Rifda Fatika Zumaira; Candraningratri Ekaputri Widodo; Hakimatul Mukaromah (Regional Development Information Center, Universitas Sebelas Maret, 2026)
Solid waste management in Magelang City has become increasingly complex due to population growth and limited landfill capacity. To support sustainable urban environmental development, the local government has implemented a 3R (Reduce, Reuse, Recycle)-based waste management system through the establishment of TPS 3R facilities. This study aims to evaluate the effectiveness of waste management practices at active TPS 3R sites in Magelang City. A quantitative approach was employed, using primary data collected through field observations and interviews, as well as secondary data from relevant documents. The evaluation covered four active TPS 3R facilities—Anggrek Potro, Dumpoh, Jurangombo, and Tidar Campur—based on five key aspects: operational techniques, institutional capacity, regulation, financing, and community participation. The results indicate that Anggrek Potro, Dumpoh, and Tidar Campur TPS 3R facilities are moderately effective, while Jurangombo TPS 3R is categorized as less effective. Despite these findings, the overall service coverage remains limited, serving only approximately 2.35% of the city area and processing about 2.29% of total waste generation. These results suggest that although TPS 3R-based waste management performs reasonably well in certain aspects, further expansion of service coverage, facility improvement, and enhanced community participation are required to achieve sustainable urban waste management in Magelang City.